Formulating a model of mobile augmented reality usage among Malaysian pre-service teachers / Nur Nabihah Mohamad Nizar - Mohamad Nizar, Nur Nabihah (2021)
The popularity of Mobile Augmented Reality (MAR) has increased in recent years. However, the potential remains underexplored in education due to the massive penetration in the entertainment industry. It promotes flexibility in learning as well as enriches students’ learning experiences. Therefore, this study aims to enhance the use of MAR and formulates a model of MAR usage for pre-service teachers. Since they are the limitations in achieving existing MAR technology resource, the present study developed a MAR technology, namely Mobile Augmented Reality Learning Cardiovascular (MARLCardio). In the context of this study, MARLCardio serves as a tool to exemplify the experiences of MAR usage. This study employs sequential explanatory research, and the data collection process were divided into three phases. The first phase involves the design and development of MARLCardio. A survey was distributed, and the responses were analysed using descriptive analysis. The second phase is highlighted to determine the acceptance level of MAR and the factors that might influence pre-service teachers’ decision to use MAR in their learning. Responses from pre-service teachers through a survey were analysed using descriptive analysis and structural equation modelling. Lastly, the third phase reflects the interview sessions of pre-service teachers. The transcript data were further analysed through thematic analysis. The results suggest that five multimedia components (video, animation, text, visuals and sound) and systematic workflows contributed to the successful development of MARLCardio. This study also found that pre-service teachers are at their moderate level in accepting the use of MAR. In addition, there are four factors that contribute to the pre-service teachers’ decision in using MAR for learning. This includes the performance expectancy (PE), effort expectancy (EE), social influences (SI) and attitude (ATT). All these factors were further used to formulate a model of MAR usage. The model suggests that the benefits gained from the use of MAR technology play a major role to increase the use of MAR. It also would determine how pre-service teachers want to perceive it, either in positive or negatives ways. At the same time, the easiness of use and support from surrounding people are also a concern for those who are not familiar with the use of MAR. It can help them to adopt the use of MAR easily. The model formulation of MAR usage perhaps is able to provide ideas and assist future research towards achieving better success of MAR usage.